Fault-tolerant architecture and implementation of a distributed control system using containers - Tamanaka, Gustavo Teruo Bernardino; Aroca, Rafael Vidal; Caurin, Glauco Augusto de Paula (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2022: Anais do XIV Simpósio Brasileiro de Robótica e XIX Simpósio Latino Americano de Robótica, 2022)
The presence of embedded devices surrounding society is clear and notable nowadays, especially in the context of the Internet of Things (IoT) and smart devices. The development of such devices and significant improvements in the capacity of microprocessors, microcontrollers, and Systems on Chip (SoCs), these devices became so powerful that they can compete with personal computer microprocessors, but using less energy and dissipating less heat. Thereby, all this processing power can be used in combine to perform intensive computing tasks in coordination with each other. The proposed architecture is constituted by general purpose hardware for embedded development such as Raspberry Pi and Beagle Bone. Also, the software architecture is based on the concept of microservices and containers encapsulation. A fault-tolerant flight control case study is shown as possible application, although the main goal focus on show how the concept can be apply for any edge intensive computer system that make use the distributed computer power to create a fault proof solution.